TextTearing: Opening White Space for Digital Ink Annotation - Yoon, Dongwook; Chen, Nicholas; Guimbretière, François (Proceedings of the 26th Annual ACM Symposium on User Interface Software and Technology, 2013)
Having insufficient space for making annotations is a problem that afflicts both paper and digital documents. We introduce the TextTearing technique for in situ expansion of inter-line whitespace and pair it with a lightweight interaction for margin expansion as a way to address this problem. The full system leverages the dynamism of digital documents and employs a bimanual design that combines the precision of pen with the fluidity of touch. Our evaluation found that a simpler unimanual variant of TextTearing was preferred over direct annotation and margin-only expansion. Direct annotation in naturally occurring whitespace was least preferred.